Fast coalescence of post-Newtonian Supermassive Black Hole Binaries in real galaxies - Sobolenko, M.; Berczik, P.; Spurzem, R.; Kupi, G. (Кинематика и физика небесных тел, 2017)
We present the results of theoretical modeling of supermassive black hole binary (SMBHB) mergers using direct 2 -body simulations with a Hermite integration scheme. The BH’s gravitational interaction is described based on the post-Newtonian (PN-terms) approximation up to the 3.5 PN-terms. We carry out a large set of runs using a parametric description of SMBHB orbits. Представлены результаты теоретического моделирования слияния двойных сверхмассивных чёрных дыр с помощью прямого 2-тельного моделирования с эрмитовской схемой интегрирования. Гравитационное взаимодействие черных дыр описывается постньютоновским приближением до 3.5 PN-терма. На основе параметрического описания орбит ДСМЧД получен большой набор моделей. Приводяться результати теоретичного моделювання злиття подвійних надмасивних чорних дір за допомогою прямого 2-тільного моделювання з ермітівською схемою інтегрування. Гравітаційна взаємодія чорних дір описується постньютонівським наближенням до 3.5 PN-терму. На основі параметричного опису орбіт ПНЧД отримано великий набір моделей.